Mitochondrially Mediated Integrin α(IIb)β(3) Protein Inactivation Limits Thrombus Growth - Liu, Fang (American Society for Biochemistry and Molecular Biology, 2013)
When platelets are strongly stimulated, a procoagulant platelet subpopulation is formed that is characterized by phosphatidylserine (PS) exposure and epitope modulation of integrin α(IIb)β(3) or a loss of binding of activation-dependent antibodies. Mitochondrial permeability transition pore (mPTP) formation, which is essential for the formation of procoagulant platelets, is impaired in the absence of cyclophilin D (CypD). Here we investigate the mechanisms responsible for these procoagulant platelet-associated changes in integrin α(IIb)β(3) and the physiologic role of procoagulant platelet formation in the regulation of platelet aggregation. Among strongly stimulated adherent platelets, integrin α(IIb)β(3) epitope changes, mPTP formation, PS exposure, and platelet rounding were closely associated. Furthermore, platelet mPTP formation resulted in a decreased ability to recruit additional platelets. In the absence of CypD, integrin α(IIb)β(3) function was accentuated in both static and flow conditions, and, in vivo, a prothrombotic phenotype occurred in mice with a platelet-specific deficiency of CypD. CypD-dependent proteolytic events, including cleavage of the integrin β(3) cytoplasmic domain, coincided closely with integrin α(IIb)β(3) inactivation. Calpain inhibition blocked integrin β(3) cleavage and inactivation but not mPTP formation or PS exposure, indicating that integrin inactivation and PS exposure are mediated by distinct pathways subsequent to mPTP formation. mPTP-dependent alkalinization occurred in procoagulant platelets, suggesting a possible alternative mechanism for enhancement of calpain activity in procoagulant platelets. Together, these results indicate that, in strongly stimulated platelets, mPTP formation initiates the calpain-dependent cleavage of integrin β(3) and associated regulatory proteins, resulting in integrin α(IIb)β(3) inactivation, and demonstrate a novel CypD-dependent negative feedback mechanism that limits platelet aggregation and thrombotic occlusion.